(untitled) (Baghdad Science Journal, 2025)
The following dilutions -710X46, -610X46, -510X46 of Bacillus thuringiensis were used for bioassay against the different larval instar of the potato tuber moth Phthorimaea operculella by the spraying method, the results showed that there was no significant influence in the percentage of egg hatching in comparison with the control. The sensitivity of larval stages was reduced with the increasing the age and exposure period. The study also showed that the larvae infected with B.t. stopped feeding, movement and a general paralysis causing the death of larva after (24-48) hours , and the larva color was changed from the natural waxy colour to brown finally to the black after death.